1998
DOI: 10.1038/bjc.1998.652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impaired renal function on the pharmacokinetics of raltitrexed (Tomudex ZD1694)

Abstract: Summary This open-label, non-randomized, parallel-group trial investigated the pharmacokinetics of raltitrexed (Tomudex, formerly ZD1 694) after a single intravenous dose of 3.0 mg m-2, comparing eight cancer patients with mild to moderate renal impairment (creatinine clearance 25-65 ml min-') with eight cancer patients with normal renal function (creatinine clearance >65 ml min-'). The primary end points were area under the plasma raltitrexed concentration-vime curve from the start of the infusion to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The present study investigated the pharmacokinetics of raltitrexed in patients with advanced solid tumours using a population pharmacokinetic approach. The findings of the pharmacokinetic properties of raltitrexed in the study were in agreement with those obtained using a conventional pharmacokinetic analysis approach [6–9]. The concentration–time profile of raltitrexed was best described by a three‐compartment pharmacokinetic model and the clearance and volume of distribution of raltitrexed were found to be in close agreement with those previously reported [8, 11].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The present study investigated the pharmacokinetics of raltitrexed in patients with advanced solid tumours using a population pharmacokinetic approach. The findings of the pharmacokinetic properties of raltitrexed in the study were in agreement with those obtained using a conventional pharmacokinetic analysis approach [6–9]. The concentration–time profile of raltitrexed was best described by a three‐compartment pharmacokinetic model and the clearance and volume of distribution of raltitrexed were found to be in close agreement with those previously reported [8, 11].…”
Section: Discussionsupporting
confidence: 89%
“…The pharmacokinetics and clinical toxicity of raltitrexed have previously been evaluated in patients with renal impairment [9]. Although a direct relationship has not been defined between creatinine clearance and the degree of clinical toxicity of raltitrexed, it was reported that the raltitrexed clearance is approximately halved in patients with mild to moderate renal function impairment [9]. These patients exhibit a significantly prolonged half‐life and a greater AUC than patients with normal renal function [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations